2010
DOI: 10.1038/ejcn.2010.259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body size and sociodemographic characteristics on differences between self-reported and measured anthropometric data in middle-aged men and women: the EPIC-Norfolk study

Abstract: Background/Objectives: To investigate the effects of body size and sociodemographic characteristics on differences between self-reported (SR) and measured anthropometric data in men and women. Subjects/Methods: This study comprises 9933 men and 11 856 women aged 39-79 years at baseline survey (1993)(1994)(1995)(1996)(1997) in the EPIC-Norfolk study (Norfolk arm of the European Investigation into Cancer and Nutrition Study). The effects of sex, measured height, weight, age group, educational level and social cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
7
34
1
Order By: Relevance
“…To mitigate this potential source of bias, we used a prediction equation to improve self-reported weight estimates [21]. Furthermore, in the EPIC Norfolk study, a subcohort of EPIC, a high correlation between self-reported and measured weight data has been shown (r = 0.97 in men and r = 0.98 in women), which means that ranking of participants according to self-reported weight was good [33]. In the two centers with measured weight at followup (Doetinchem and Norfolk), observed associations were in the same direction as overall with only a few exceptions (Online Resource 1) adding confidence to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this potential source of bias, we used a prediction equation to improve self-reported weight estimates [21]. Furthermore, in the EPIC Norfolk study, a subcohort of EPIC, a high correlation between self-reported and measured weight data has been shown (r = 0.97 in men and r = 0.98 in women), which means that ranking of participants according to self-reported weight was good [33]. In the two centers with measured weight at followup (Doetinchem and Norfolk), observed associations were in the same direction as overall with only a few exceptions (Online Resource 1) adding confidence to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, the validity of waist and hip circumferences have seldom been evaluated, resulting in lower correlations between self-reported and direct measurements (ranging from 0.62 to 0.89). 2,5,8,9 The Mexican Teachers' Cohort (MTC), also known as ESMaestras (Spanish acronym), is an ongoing prospective study aimed at evaluating the relationship of dietary and lifestyle factors and chronic diseases. As the largest cohort study in Latin-America and among Hispanics, the MTC offers a unique sample from which to assess the validity of self-reported anthropometry among Mexican women due to its large sample size, wide age range (25 to 84 years at enrollment) and the economically and culturally diverse origin of participants.…”
Section: Artículo Originalmentioning
confidence: 99%
“…Information on lifetime use of alcoholic beverages was not available for the study centres in Naples (Italy), Bilthoven (The Netherlands), Sweden and Norway (n ¼ 116 149). We also excluded the health conscious part of the Oxford cohort (Great Britain) (n ¼ 47 651; 85% of the British cohort)) and the French cohort (n ¼ 51 267), as anthropometry was self-reported (Park et al, 2011). Therefore, 258 177 (99 381 men and 158 796 women) participants from Denmark (Aarhus, Copenhagen), Germany (Heidelberg, Potsdam), Greece, Italy (Florence, Varese, Ragusa, Turin), The Netherlands (Utrecht), Spain (Asturias, Granada, Murcia, Navarra, San Sebastian) and the United Kingdom (Cambridge, Oxford), representing 50% of the original cohort, were eligible for this analysis.…”
Section: Study Populationmentioning
confidence: 99%